Analysis of the Mainstreaming Program for Religious Moderation for Students: Study of Ministerial Regulation of Education and Culture Number 45 of 2014 - Dudiyono Dudiyono; Slamet Wahyudi; Kholid Mawardi (Indonesian Academy of Social and Religious Research (IASRR), 2022)
Indonesia as an archipelagic country, has ethnic, linguistic, religious, cultural and social statuses. Religious moderation is an essential aspect in managing religious life in a plural and multicultural Indonesian society. In education discourse, religious moderation is an interesting issue, where currently, people in Indonesia have given serious attention to religious moderation. The purpose of this study is to find out what aspects of the Religious Moderation Mainstreaming program for students by examining Permendikbud No. 45 of 2014 concerning school uniforms for students at primary and secondary education levels. The research method is qualitative with a literature study approach. The conclusions in this study are 1) The mainstreaming program of religious moderation in schools. Where educational institutions can play a strategic role in religious moderation. 2) School uniforms as religious moderation, 3) School uniforms and religious rights, Identity in the form of this uniform initiates people's views of the religion adopted by students, and 4) School uniforms and attitudes of nationalism in religious moderation as a culture of tolerance which is described through respecting others, nationalism is related to the student's commitment to prioritizing the national interest.